Penyuluhan Tentang Imunisasi Dasar Lengkap Di Puskesmas Kapasa Kota Makassar: Penyuluhan Tentang Imunisasi Dasar Lengkap Di Puskesmas Kapasa Kota Makassar - Nurhikmah Nurhikmah; Rusli Taher; Muliyana; Nur Aliya Arsyad; Reskiawati Azis (COVIT (Community Service of Health), 2022)
Low complete basic immunization coverage is still a very difficult problem to deal with. Government programs in an effort to improve the degree of children's health that is before the child is one-year-old basic immunization should be given in full according to his age. In this condition, the immune system is expected to work optimally with the effect caused to a minimum. This devotion aims to increase public knowledge about complete basic immunization so that basic immunization coverage can increase. The methods used are lectures and discussions. The implementation in Kapasa Public Health Center with the number of participants as many as 30 mothers. From the results of the extension, there is an increase in the knowledge and understanding of mothers so that it is expected that this training activity can be carried out in all the work areas of Public Health Center with government support.